2013
DOI: 10.1158/0008-5472.can-12-2449
|View full text |Cite
|
Sign up to set email alerts
|

Booster Vaccinations against Cancer Are Critical in Prophylactic but Detrimental in Therapeutic Settings

Abstract: Although cancer vaccines are in the clinic, several issues remain to be addressed to increase vaccine efficacy. In particular, whether how and how frequently a patient should be boosted remains to be defined. Here, we have assessed the ability of dendritic cell (DC)-based vaccines to induce a long-lasting tumorspecific CTL response in either prophylactic or therapeutic settings by taking advantage of transplantable and spontaneous mouse tumor models. Implementing a 24-hour ex vivo intracellular cytokine produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
4
17
0
Order By: Relevance
“…We have also found that boosting has a considerable impact on the pool of IFNγ-producing cytotoxic CD8 + T CM cells, which exceeds by more than 2-fold the pool detected in non-boosted mice 4 . This holds true for both exogenous and endogenous antigens, which are recognized by T cells bearing high- and low-affinity TCR, respectively 4 …”
mentioning
confidence: 58%
See 3 more Smart Citations
“…We have also found that boosting has a considerable impact on the pool of IFNγ-producing cytotoxic CD8 + T CM cells, which exceeds by more than 2-fold the pool detected in non-boosted mice 4 . This holds true for both exogenous and endogenous antigens, which are recognized by T cells bearing high- and low-affinity TCR, respectively 4 …”
mentioning
confidence: 58%
“…When mice received booster injections at earlier time points (i.e., after a 2-week interval; tight boosting), a reduced amount of T CM cells was found in the spleen and the survival curve of these mice resembled that of mice that received only the priming injection 4 . Unexpectedly, also boosting with complete and incomplete Freund’s adjuvants (CFA and IFA, respectively), even when performed at 4-week intervals, was detrimental for the pool of T CM cells 4 . These findings are in line with a recent report showing that IFA leads to the trapping of tumor-specific CD8 + T cells at the vaccination site, where they become dysfunctional and undergo apoptosis 6 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…No clear comparison has been made, and therefore no strong conclusions can be drawn. According to mouse studies and some clinical trials, vaccination seems to be critical, but boosting strategies of subjects with residual disease or with tumor recurrence, should be carefully revisited (68). …”
Section: Vaccination Strategiesmentioning
confidence: 99%